White light emission under 980 nm and Judd-Ofelt analysis of tellurite-zinc glasses doped with Er3+-Yb3+-Tm3+ - Calderón, Gaston Lozano (2020)
In this dissertation, tellurite-zinc glasses doped with Tm3+, Yb3+ and Er3+ were fabricated by conventional melt-quenching method and characterized by absorption spectroscopy, refractive index, lifetime measurements, excitation, luminescence and up-conversion spectroscopy. Tunable white to blue light emission based on the colour mixing of red, green and blue light was observed in the triply-doped samples via up-conversion under 980 nm and by adjusting the laser excitation intensity. The balancing of the relative intensity of each colour is provided by the energy transfer process between the rare-earth ions. Moreover, luminescence spectroscopy was performed with a 405 nm laser to further understand the energy transfer mechanism. According to the Judd-Ofelt theory, the intensity parameters (Ω2, Ω4 and Ω6) of Er3+ and Tm3+ for all samples present the trend Ω2 < Ω4 < Ω6. These parameters are related to the bonding and local structure in the vicinity of the rare-earth ions, which give information regarding to physical and chemical properties. The spectroscopic parameters were calculated with the Judd-Ofelt theory and the energy transfer micro-parameters (critical radius of interaction and energy transfer coefficient) were determined by the Dexter model. Such results shall be used to give a comprehensive explanation for the energy transfer process between these rare earth ions.